Molecular investigation of BVDV in cattle in Thi-Qar Province, Iraq. - Gali, Ebtessam Algum; Basim A. Jarullah, (University of Thi-Qar Journal of Science, 2023)
Bovine viral diarrhea virus (BVDV) is a complicated ruminant pathogen that naturally infects cattle, goats, sheep, buffalo, pigs, camelids, and wild ruminants. BVDV infection causes serious financial losses, either directly due to high rates of mortality and morbidity brought on by fatal mucosal disease and immunosuppression. From September 2022 to May 2023, blood samples (225) were randomly collected from unvaccinated cattle from various regions within Thi-Qar province, Iraq. 5?-untranslated region (UTR) amplification by nested RT-PCR results showed that the distribution of bovine viral diarrhea virus in Thi-Qar province was 19.11% (43 out of 225). These results show no statistically significant differences in the bovine viral diarrhea virus distribution between geographical regions and study months (P >0.05).